Photoperiod and growth regulators on in vitro shoot induction in Heliconia latispatha - Rodrigues, Antonio Anderson de Jesus; Santos, Eder de Oliveira; Carvalho, Ana Cristina Portugal Pinto de (Ornamental Horticulture, 2016)
Considering the growing economic importance of tropical flowers and the advantages of techniques applied to the in vitro cultivation of these plants, it is necessary to carry out studies to evaluate growth in species such as Heliconia latispatha. The aim of this study therefore, was to evaluate in vitro shoot induction for different concentrations of BAP and NAA and as a function of the photoperiod. Explants from zygotic embryos were inoculated in MS medium containing different concentrations of BAP (0.0, 0.5, 1.0, 1.5, 2.0 or 2.5 mg L-1), with the cultures kept in a growth room at a temperature of 24.0 ± 2.0° C, under a photoperiod of 12 and 16 hours of light and a light intensity of 30 μmol m-2 s-1. At 21, 28, 35, 42 and 49 days after inoculation, the number of shoots per explant was evaluated. The treatment at the BAP concentration that gave the best multiplication rate (2.5 mg L-1) was set, and was tested in a further trial with different concentrations of NAA (0.0, 0.2, 0.4, 0 6, 0.8 or 1.0 mg L-1) under the same conditions as the previous experiment. The experimental designs were completely randomised, with five replications, and analysed in a 6 x 2 factorial. The data were submitted to analysis of variance and regression. No significant differences were seen in relation to the photoperiod or its interaction with the cytokinin and auxin under test. Multiplication was greater in the presence of 2.5 mg L-1 BAP, which gave a rate of 1.25 shoots/explant at 49 days of in vitro culture. The association of this BAP dosage with 1.0 mg L-1 NAA was even more efficient, producing 1.83 shoots per explant at 30 days of growth. The use of BAP together with NAA is beneficial to the induction of shoots in H. latispatha.